Internship Quality and Employability: The Mediating Role of Career Entry-Worries - Khairina Salsabilla; Syahrizal (Jurnal Informatika Ekonomi Bisnis, 2026)
The purpose of this study was to determine the influence of perceptions of internship quality on students' perceptions of work ability, with concerns about entering the workforce as a mediating variable in students of the Faculty of Economics and Business, Padang State University. A quantitative causal approach was employed, and stratified proportional sampling was used to obtain a total of 238 participants. A Likert-scale questionnaire was used, and data analysis was performed using SmartPLS 3. The results show that perceived internship quality positively and significantly affects perceived employability and negatively affects career-entry worries. Career-entry worries also negatively and significantly influence perceived employability. Furthermore, it was found that Career Entry Worries mediate the relationship between Perception of Internship Quality and Perception of Employability. These findings highlight the importance of high-quality internship experiences in enhancing employability by reducing psychological concerns during the transition to the workforce.